Functional imaging of cortical feedback projections to the olfactory bulb - Rothermel, Markus; Wachowiak, Matt (Frontiers in Neural Circuits, 2014)
Processing of sensory information is substantially shaped by centrifugal, or feedback, projections from higher cortical areas, yet the functional properties of these projections are poorly characterized. Here, we used genetically-encoded calcium sensors (GCaMPs) to functionally image activation of centrifugal projections targeting the olfactory bulb (OB). The OB receives massive centrifugal input from cortical areas but there has been as yet no characterization of their activity in vivo. We focused on projections to the OB from the anterior olfactory nucleus (AON), a major source of cortical feedback to the OB. We expressed GCaMP selectively in AON projection neurons using a mouse line expressing Cre recombinase (Cre) in these neurons and Cre-dependent viral vectors injected into AON, allowing us to image GCaMP fluorescence signals from their axon terminals in the OB. Electrical stimulation of AON evoked large fluorescence signals that could be imaged from the dorsal OB surface in vivo. Surprisingly, odorants also evoked large signals that were transient and coupled to odorant inhalation both in the anesthetized and awake mouse, suggesting that feedback from AON to the OB is rapid and robust across different brain states. The strength of AON feedback signals increased during wakefulness, suggesting a state-dependent modulation of cortical feedback to the OB. Two-photon GCaMP imaging revealed that different odorants activated different subsets of centrifugal AON axons and could elicit both excitation and suppression in different axons, indicating a surprising richness in the representation of odor information by cortical feedback to the OB. Finally, we found that activating neuromodulatory centers such as basal forebrain drove AON inputs to the OB independent of odorant stimulation. Our results point to the AON as a multifunctional cortical area that provides ongoing feedback to the OB and also serves as a descending relay for other neuromodulatory systems.